2008
DOI: 10.2310/7290.2008.0006
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Head and Neck Tumors in Vivo Using Near-Infrared Fluorescent Transferrin Conjugate

Abstract: Transferrin receptor (TfR) is overexpressed in human head and neck squamous cell carcinomas (HNSCCs). This study was carried out to investigate the feasibility of imaging HNSCC by targeting TfR using near-infrared fluorescent transferrin conjugate (TfNIR). Western blot analysis of four HNSCC cell lines revealed overexpression of TfR in all four lines compared with that in normal keratinocytes (OKFL). Immunocytochemistry further confirmed the expression of TfR and endocytosis of TfNIR in JHU-013 culture cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Links between excess iron and cancer are also suggested by the efficacy of dietary iron deprivation [77] and iron chelators [78] in cancer therapy. In the early 1980’s it was observed that levels of transferrin receptor 1 (TfR1) are elevated in cancer, and use of TfR1 as a targeting ligand in the design of anti-cancer drugs was proposed [79,80]. …”
Section: Diseases Of Iron Metabolismmentioning
confidence: 99%
“…Links between excess iron and cancer are also suggested by the efficacy of dietary iron deprivation [77] and iron chelators [78] in cancer therapy. In the early 1980’s it was observed that levels of transferrin receptor 1 (TfR1) are elevated in cancer, and use of TfR1 as a targeting ligand in the design of anti-cancer drugs was proposed [79,80]. …”
Section: Diseases Of Iron Metabolismmentioning
confidence: 99%
“…A maximum signal intensity of the tumors was detected between 90 and 120 min after the injection and a high fluorescent ratio of tumor to muscle was obtained. [80]. Keereweer et al injected tumor-specific near-infrared fluorescence agents targeting glucose transporter system (CW800 2-DG) in mice with tongue tumors and cervical lymphadenopathy.…”
Section: Head and Neck Image Guided Surgerymentioning
confidence: 98%
“…This peptide has been conjugated to multiple fluorophores or coupled with quantum dots to visualize avb3 integrin positive head and neck squamous cell carcinoma [75][76][77][78][79]. Transferrin receptor (TfR) is also appreciated to overexpress in the head and neck cancer and often associated with poor prognosis [80]. An in vivo study was conducted to determine the feasibility of targeting TfR using NIR fluorescent transferrin conjugate.…”
Section: Head and Neck Image Guided Surgerymentioning
confidence: 99%
“…TfR antibody was labeled with Alexa-488. TfRNIR was injected into immunodeficient mice bearing HNSCC via tail vein, and animals were imaged using IVIS every 10–30 min up to at least 6 h [ 61 . The results indicated a potential use of anti-CD147 and TfR antibody for noninvasive head and neck tumor imaging.…”
Section: Recent Advances In Endoscopic Molecular Imagingmentioning
confidence: 99%